EXPORT DIVERSIFICATION AND ECONOMIC GROWTH IN ASEAN - Sunaryati, Sunaryati (Jurnal Ekonomi & Studi Pembangunan, 2015)
Abstract: This paper tries to assess empirically the relationship between export diversification and economic growth on selected countries in ASEAN. Using annual data or time-series over the period 1989 to 2010 and econometric techniques (Granger causality and cointegration) are applied to test the relationship between export diversification and economic growth. The result show that, in case of Indonesia and Malaysia, there are exist uni-directional causality from GDP to export diversification. For Singapore and Thailand, the results show that there are no causal relationship between export diversification and economic growth.Abstrak: Tulisan ini mencoba mengkaji secara empiris hubungan antara diversifikasi ekspor dan pertumbuhan ekonomi di negara yang dipilih di ASEAN. Dengan menggunakan data tahunan atau time series selama periode 1989 sampai 2010 dan teknik ekonometrik (Granger kausalitas dan kointegrasi) yang diterapkan untuk menguji hubungan antara diverÂsifikasi ekspor dan pertumbuhan ekonomi. Hasil penelitian menunjukkan bahwa, dalam kasus Indonesia dan Malaysia, ada ada uni-directional kausalitas dari PDB untuk diversifiÂkasi ekspor. Untuk Singapura dan Thailand, hasil menunjukkan bahwa tidak ada hubungan sebab akibat antara diversifikasi ekspor dan pertumbuhan ekonomi.